ACLED Conflict Index G5 Sahel (2018-2023) - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
This dataset contains the ACLED conflict index, its classification, and related underlying dimensions and rankings of deadliness, danger, diffusion, and fragmentation for the 279 second-level administrative areas of Mauritania, Mali, Burkina Faso, Niger, and Chad between 2018 and 2023. Following a slightly modified version of ACLED's conflict index methodology, the dataset is generated based on ACLED’s curated dataset for Africa (5 January 2024) and United Nations Office for the Coordination of Humanitarian Affairs's (OCHA) geographic dataset for the Sahel (including P-codes).